Interactions between water, energy, food and environment: evolving perspectives and policy issues - Hellegers, Petra J.G.J.; Zilberman, D.; Steduto, P.; McCornick, Peter G. (IWA Publishing, 2008)
Major changes are occurring with far reaching implications for the existing equilibria or disequilibria in the water-energy-food-environment interface. The increased demand of energy worldwide will reflect directly and indirectly on water-dependent systems. Direct implications will come from higher energy prices, which make extraction and conveyance of water more costly. Indirect implications will be in the form of demand for alternative energy sources. It triggers demand for hydropower and remains a major driver—along with some environmental policies—for biofuel expansion. The key question is how these effects may alter water allocation and influence food security, rural poverty and environmental sustainability. This paper sets the background and context of this special issue by highlighting some of the major water-related policy issues related to the subject and provides an overview and synthesis of the papers in this special issue. Besides offering insight into how these papers address these questions in the practical context of few selected countries and basins, this paper also indicates some key areas for future research on the subject.